2018
DOI: 10.1155/2018/7854052
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Interaction between Soil and the Five-Claw Combination of a Mole Using the Discrete Element Method

Abstract: A mole is a born digger spending its entire existence digging tunnels. The five claws of a mole's hand are combinative to cut soil powerfully and efficiently. However, little was known in detail about the interaction between the soil and the five-claw combination. In this study, we simulated the soil cutting process of the five-claw combination using the discrete element method (DEM) as an attempt for the potential design of soil-engaging tools to reduce soil resistance. The five-claw combination moved horizon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 30 publications
3
20
0
Order By: Relevance
“…The rotary tillage blade started to break the soil after the whole body of the blade entered the soil, and then, soil wedge was formed in front of the blade as shown in Figure 15 . Based on the previous study [ 20 ], the soil rupture distance ratio of the five-claw combination was about 19.6% smaller than the predicted values of simple blades. It indicated that the soil failure wedge of the BB-1 was significantly diminished so that a lower force was needed for soil shearing.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…The rotary tillage blade started to break the soil after the whole body of the blade entered the soil, and then, soil wedge was formed in front of the blade as shown in Figure 15 . Based on the previous study [ 20 ], the soil rupture distance ratio of the five-claw combination was about 19.6% smaller than the predicted values of simple blades. It indicated that the soil failure wedge of the BB-1 was significantly diminished so that a lower force was needed for soil shearing.…”
Section: Discussionmentioning
confidence: 79%
“…The lateral spacing between two adjacent claws is labelled as Δ x . All of the parameters were recorded and presented in Table 2 according to the previous literature [ 20 ]. From the studies by Godwin [ 21 , 22 ], the working depth/width ratio and the tine spacing are the important parameters to determine the categories of blades, soil failure pattern, and soil forces.…”
Section: Geometric Characteristics Of Five Fore Claws Of Mole Ratsmentioning
confidence: 99%
See 1 more Smart Citation
“…Shi et al [16] established the 3D models of crop stalks and cutters by using response surface methodology to determine the optimal combination of the kinematic parameters of the cutter at a cutting speed of 1.6 m/s, cutting angle of 15°, and working speed of 1 m/s. Biomimetic technology has recently been applied to optimize the design of traditional agricultural machinery and to improve its energy utilization [17][18][19][20]. It combines biological principles with engineering problems for developing solutions.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the development of bionics has injected new vitality into agricultural machinery drag reduction technology [27][28][29]. Natural organisms have evolved excellent functions and unique geometric structures over billions of years, and among them, animals that are good at digging have evolved superior digging organs.…”
Section: Introductionmentioning
confidence: 99%